EFL STUDENTS’ ANXIETY FACTORS IN DOING ORAL PUBLIC EXAMINATION : INTERNAL OR EXTERNAL FACTOR? - Syafryadin Syafryadin; Ida Yulianawati (Eltin Journal : Journal of English Language Teaching in Indonesia, 2023)
Anxiety is a psychological issue that must be noticed in learning English. Students feel anxious about doing public speaking, like oral presentations. Surely, it may be caused by internal and external factors. Therefore, this study aimed to find out the factors that caused EFL students’ anxiety in doing oral public examinations. A mixed method was employed to conduct this research. The sample of this research was twenty-four students of doctoral program who do oral public examinations in 2022. The instruments were questionnaire and interview guideline. The data were analyzed quantitatively and qualitatively. In quantitative data, simple calculation with mean score and percentage were used in this research, while in qualitative data, several steps were undertaken namely reducing, displaying and concluding the data. The result showed that students felt anxiety were caused by internal and external factor. However, it was dominated by internal factor. It can be proved by looking at the result of questionnaire namely mean scores of students who were affected by it is 40.6%, while 33.34% for external factor. Besides, it was also supported by interview result. In short, these factors could be obstacles for students to do oral presentation. These must be noticed, known and anticipated by the students.